Implementasi Model Pembelajaran Berbasis Teams Games Turnamen (TGT) dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran PAI - Maimanah, Miratul; Al Firdaus , Jihan Millah; El-Yunusi, Muhammad Yusron Maulana (Jurnal Ilmu Pendidikan, 2024)
This research departs from the problem from the results of library research regarding the lack of interest of students in PAI learning subjects. The teaching and learning model developed by Robert Slavin is Teams Games Tournament, which is a learning method that combines study groups with team competitions. It also cannot be used to improve learning of various concepts for skills. Learning using this method will stimulate student activity, because in the Teams Games Tournament all students are required to actively voice their opinions, both lower group students and upper group students are required to work together to solve the problems given in learning. This research aims to determine the Teams Games Tournament cooperative learning model in students' interest in learning in PAI subjects. The research method used is qualitative description with literature study. The results of this research are that the application of this learning model has a positive impact on students' interest in learning Islamic Religious Education. The conclusion of this research is that the TGT learning model can increase students' interest in learning. This can be seen from the increase in students' PAI reasoning abilities and the increase in students' PAI connection abilities.